Successful treatment of amniotic fluid embolism complicated by disseminated intravascular coagulation with rivaroxaban: A case report - Wu, Hai-Di (Medicine (Baltimore), 2020)
RATIONALE: An amniotic fluid embolism (AFE) is a rare, lethal syndrome that is commonly associated with disseminated intravascular coagulation (DIC). Anticoagulation therapy is the most important strategy to inhibit excessive activation of the coagulation cascade in patients with AFE and DIC. At present, treatment of AFE with rivaroxaban has not been reported. PATIENT CONCERNS: We report a 37-year-old woman (gravida 2, para 1) at 39 weeks’ gestation with irregular contractions of the uterus was admitted to the obstetrical department. Ten minutes after the spontaneous rupture of the membranes, the patient complained of dyspnea and dysphoria and exhibited cyanosis of her lips. The patient's blood pressure decreased and heart rate increased rapidly, and 2100 mL of unclotted blood flowed from her vagina within 1 hour. Her platelet count dropped to 21 × 10(−9)/L, and the results from routine coagulation tests, and D-dimer and fibrin degradation product tests were obviously abnormal. DIAGNOSES: According to the current research consensus, AFE with DIC should be considered immediately when sudden cardiovascular collapse occurs around the time of labor and delivery, followed by the development of coagulopathy and hemorrhage. INTERVENTIONS: In addition, the variety of supportive treatments, rivaroxaban was used in anticoagulant therapy. OUTCOMES: At follow-up 30 and 60 days, there were no complaints of discomfort or abnormal laboratory assays. The patient recovered completely. LESSONS: : This case highlights that rivaroxaban, as a direct inhibitor of activated factor Xa, demonstrates a good therapeutic efficacy for treating AFE with DIC.